The Effect of Guided Question Technique on Students’ Writing Ability in Descriptive Text - Rizka Indriani; zahrida .; Mei Hardiah (Journal of English Education and Teaching, 2019)
The objective of this research is to find out whether or not there is a significant effect using guided question technique on students’ writing ability in descriptive text. This research is a quasi experimental design. The population of this research is the seventh grade students at SMPN 3 Kota Bengkulu. The sample in this research are about 60 students divided into 2 classes, VII 2 consists of 30 students as the experimental group and VII 3 that consist of 30 students as the control group. The treatment is given only for the experimental group. The data are collected by using two writing tests: pre-test and post-test. The result of the research showed the mean score of experimental group (31.34) was higher than mean score of control group (23.35). This indicated that the guided question technique could give a significant positive effect to the students’ writing ability in descriptive text.